Improved quality and quantity of written feedback is associated with a structured feedback proforma - Phil Newton (Journal of Educational Evaluation for Health Professions, 2012)
We changed the structure of the feedback proforma used to give written feedback to medical students. The change was from a blank form to a structured form with lead-in questions. We found that use of the structured form was associated with an improvement in the quality and quantity provided.